Meta-analytic evidence on the efficacy of hypnosis for mental and somatic health issues: a 20-year perspective - Rosendahl, Jenny; Alldredge, Cameron T.; Haddenhorst, Antonia (Frontiers in Psychology, 2024)
Introduction Documented use and investigation of hypnosis spans centuries and its therapeutic use has received endorsement by multiple medical associations. We conducted a comprehensive overview of meta-analyses examining the efficacy of hypnosis to provide a foundational understanding of hypnosis in evidence-based healthcare, insight into the safety of hypnosis interventions, and identification of gaps in the current research literature. Methods In our systematic review, meta-analyses of randomized controlled trials on the efficacy of hypnosis in patients with mental or somatic health problems compared to any control condition published after the year 2000 were included. A comprehensive literature search using Medline, Scopus, PsycINFO, The Cochrane Library, HTA Database, Web of Science and a manual search was conducted to identify eligible reviews. Methodological quality of the included meta-analyses was rated using the AMSTAR 2 tool. Effect estimates on various outcomes including at least three comparisons (k ≥ 3) were extracted and transformed into a common effect size metric (Cohen’s d). If available, information on the certainty of evidence for these outcomes (GRADE assessment) was obtained. Results We included 49 meta-analyses with 261 distinct primary studies. Most robust evidence was reported for hypnosis in patients undergoing medical procedures (12 reviews, 79 distinct primary studies) and in patients with pain (4 reviews, 65 primary studies). There was a considerable overlap of the primary studies across the meta-analyses. Only nine meta-analyses were rated to have high methodological quality. Reported effect sizes comparing hypnosis against control conditions ranged from d = −0.04 to d = 2.72. Of the reported effects, 25.4% were medium (d ≥ 0.5), and 28.8% were large (d ≥ 0.8). Discussion Our findings underline the potential of hypnosis to positively impact various mental and somatic treatment outcomes, with the largest effects found in patients experiencing pain, patients undergoing medical procedures, and in populations of children/adolescents. Future research should focus on the investigation of moderators of efficacy, on comparing hypnosis to established interventions, on the efficacy of hypnosis for children and adolescents, and on identifying patients who do not benefit from hypnosis. Clinical Trial Registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023395514, identifier CRD42023395514